Peptide-induced conformational change of the class I heavy chain. - Elliott, T; Cerundolo, V; Elvin, J; Townsend, A (1991)
There is evidence that peptide ligands take part in the assembly of class I molecules. In particular, addition of peptides to extracts of the mutant cells RMA-S and .174/T2, in which stable assembly of class I does not occur, results in a conformational change in the class I heavy chain and stable association of the heavy chain with beta 2-microglobulin (beta 2m). Thus specific peptides may stabilize or induce a conformational change in the class I heavy chain that results in a rise in the binding affinity of the heavy chain for beta 2m (Fig. 1a). Here we show that peptides have two cooperative roles in class I assembly. Specific short peptides (9-10 amino acids) can induce folding of the heavy chain in the absence of beta 2m. Both short (nine amino acids) and longer sequences (15 amino acids) can stabilize performed low-affinity complexes of heavy chain and beta 2m. To alter the conformation of free heavy chains, the peptides must be exactly the correct size, and they are found to correspond to the sequences isolated from infected cells. This property may therefore be the basis for selection of epitopes presented in vivo.